Refugee agency in secondary mobility decision-making: a systematic literature review - Kavak, Sinem; Hamza, Mo; Gammeltoft-Hansen, Thomas; Stone, Russell A. (Frontiers in Human Dynamics, 2024)
Decisions made by millions of refugees about where to go, how to make a living and how to secure a future are fundamental drivers of secondary movements. While a substantial body of literature addresses factors contributing to migrants' decision-making, a comprehensive understanding of the central role of refugees in secondary mobility decision-making, including agency and strategies employed, remains underexplored. This is partly due to the belief that refugees are constrained by external and structural factors and cannot exercise agency, which we challenge. This article provides a systematic analysis of the literature on refugees' secondary mobility decision-making processes. Using a systematic literature review (SLR) methodology, it presents an indepth analysis of 40 peer-reviewed, English-language research articles selected from the Web of Science and Scopus databases published before September 2022. The article critically examines the drivers, prevailing dichotomies and conceptual frameworks surrounding refugee categorisation, agency, and mobility. By synthesising a wide range of literature, our paper presents emerging alternative concepts and frameworks that shed light on the complex dynamics of decision-making.